Best Answer


User Avatar

Wiki User

โˆ™ 2010-04-08 09:36:10
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

See all cards

Steel Tip Darts Out Chart

96 cards





See all cards

Add your answer:

Earn +20 pts
Q: 0 equals 5c-6 what is the value of c?
Write your answer...
Related questions

What is c in y equals mx plus c?

It is the intercept: the value that y takes when x = 0

If x equals a-b y equals b-c z equals c-a then the value of x plus y plus z x plus y plus z is?

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0

What is the answer to A plus B plus C equals A times B equals C?

A=0 b=0 c=0

What is the value of c divided by 30 that equals 12?

The value of c/30 that equals 12 is 12 . In order to make that value, 'c' must be 360 .

What is the argument that A equals B B equals C so A equals C?

A=B , A-B=B-B , A-B =0 B=C , B-B=C-B, 0=C-B So A-B=0 but also C-B=0 A-B=C-B ...add +b ...A-B+B=C-B+B , A=C

How did 169 equals C squared?

Because the value of C equals 13

0.04 times c plus 1.6 equals 0 c equals?

0.04c + 1.6 = 00.04c = -1.6c = -40

What is the value of 0 in c?

the value of 0 is '1'.

What is c2-2c plus 5 equals?

It depends on the value of c. If c = 0 then 0-0+5 = 5 If c = 1 then 1-2+5 = 4 If c = 2 then 4-4+5 = 5 and so on.

What will be the value of b when a equals 26?

that depends on what the value of c is.

What can you say about the graph of Ax plus By equals C if B is equal to zero?

If B=0, then the graph does not depend on the value of y. This is a vertical line at x = C/A

What is the content of result after execution of the following cobol instruction the start value of result is 0 perform varying c from 1 by 1 until c equals 6 compute result equals result plus 1 end?

The result is 7.

What is a plus c-b if a equals 3 b equals 5 and c equals 2?

a + c - b = 3 + 2 - 5 = 5 - 5 = 0

What is the value of c when the line y equals x plus c is a tangent to the curve y equals 3 -x -5x squared?


If a x b equals 2 b x c equals 24 c x a equals 3 and a b c are all positive what is the value of a plus b plus c?


What is the value of k The equation x2-10x k0 has only one solution for x what is the value of k?

For the equation x2- 10x - k equals 0, you can solve this by knowing that if there is only one solution then the discriminant b2 - 4ac must be equal to 0. In this equation, a is 1, b is 10 and c is k This equation becomes 100 - 4k equals 0, and k is 25.

Ax plus bx plus c equals 0?

x = -c/(a+b), provided a+b is not 0

If a equals positive and b equals negative and c equals zero how many solutions does a Quadratic Equation have?

Two: one is 0, the other is -b/a ax2 + bx + c = 0, but c = 0 ⇒ ax2 + bx + 0 = 0 ⇒ ax2 + bx = 0 ⇒ x(ax + b) = 0 ⇒ x = 0 or (ax + b) = 0 ⇒ x = -b/a

What does c mean in y equals mx plus c?

c is any constant value

What is 0 degrees c in f?

0 Celsius equals 32 Fahrenheit

How do you solve for c in equation 3x2 plus 17x plus c equals 0?

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

If a plus b plus c not equal to 0 then a divided by b plus c equals b divided by c plus a equals c divided by a plus b prove that a equals b equals c?

Because there is no way to define the divisors, the equations cannot be evaluated.

What is the value of c if the line y equals x plus c is a tangent to the curve y equals 3 -x -5x squared?


A plus b equals c times c equals c times a?

well the only answer i can so far come up with is: a=1 b= -1 c=0 so then (a+b)=(c*c)=(a*c) ...............(0)=(0)=(0) ......................0 ok if that is what your looking for Great! just know that i am not a math wiz. :)

Why does the logical statement a equals b implies ac equals bc require that c not be zero?

To get rid of c from both sides you divide by c so c can't be 0